Impact of Market Risk Premium on Fair Share Value Exploration - Alasadi, Bushra Mohamed Sami (Research Parks Publishers, 2024)
This research explores the influence of the market risk premium on the fair value of shares traded on the Iraq Stock Exchange, employing the CAPM model to estimate the required rate of return. The CAPM model incorporates the risk-free rate (RF), market portfolio return (RM), and beta-processed risk premium. The study aims to quantify the impact of the risk premium on fair value, a critical component in determining the required rate of return. Statistical analysis, including correlation coefficients and regression analyses, was conducted to examine the relationships among the variables. The results indicate a direct one-to-one relationship between the risk premium and the intrinsic value of shares. This study fills a knowledge gap in understanding how market risk premiums affect share valuation, providing insights for investors and policymakers.